ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH GO PUBLIK - Lusiana, Lusiana (Jurnal Ekobistek, 2014)
Abstract : Analysis Before and After Go Public at. Sources Alfaria Trijaya Tbk. The purpose of this study is to find out how it is important to know the financial performance before and after going public at PT. Sources Alfaria Trijaya Tbk. The variables of this reserch consists of Financial Ratios (Likuidas, Solvency, Profitability) and financial statements before and after going public. In this reserch the authors use data collection techniques with documentation of secondary data. Anlisis tool that I use in this thesis is a qualitative and quantitative analysis. From the results of this study in 2006 until 2011 ( before and after go public), On Liquidity ( Current Ratio, Quick Ratio and Ratio Current Assets and Total Assets ), In Solvency Ratio ( Debt Ratio over Capital and Debt Ratio over Assets ), and Profitability Ratio ( Profit margin, Turn Over Assets, and Contribution Margin Ratio ) overall of financial performance unhealthy. Financial performance stay healthy only on quick ratio in 2006, debt ratio over assets after go public, and contribution margin after go public. Finally, the authors suggest PT. Sources Alfaria Trijaya Tbk to improve the company's financial performance and better management should also be solely responsible for investors over the next decisions to be taken. Keywords: Financial performance